2017
DOI: 10.1097/crd.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pregnancy in Patients With Congenital Long QT Syndrome

Abstract: Congenital long QT syndrome (LQTS) is a disorder of myocardial repolarization and is characterized by a prolonged QT interval on an electrocardiogram. A prolonged QT predisposes patients to an increased risk of syncope and sudden cardiac death secondary to polymorphic ventricular tachycardia. Several mutations linked to the LQTS have been identified, the most common of which have been found in the potassium channel KCNQ1 (LQT1) and hERG (LQT2) genes and in the sodium channel SCN5A (LQT3) gene. Female sex is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…This discrepancy may be due to the fact that all of the monkeys in this study were bred in cages, and their exercise load and diet differed from those of humans. It has also been reported that human females have a higher risk of long-QT syndrome due to the increased levels of progesterone during pregnancy [ 7 ]. It is thought that progesterone is one of the factors for heart disease in women.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to the fact that all of the monkeys in this study were bred in cages, and their exercise load and diet differed from those of humans. It has also been reported that human females have a higher risk of long-QT syndrome due to the increased levels of progesterone during pregnancy [ 7 ]. It is thought that progesterone is one of the factors for heart disease in women.…”
Section: Discussionmentioning
confidence: 99%
“…β-receptor blockers are effective in reducing life-threatening CE in iLQTS and therefore should be continued during pregnancy and postpartum as pregnant iLQTS women are at a risk to develop CE [8-10, 17, 45]. β-receptor blockers are not teratogenic, but they are categorized by former FDA category as “C,” whereas atenolol is categorized as “D.” They can cause IUGR commonly and additionally bradycardia, apnea, hypoglycemia, and hyperbilirubinemia have been reported in the newborn infant [17-20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the birth weight for newborns of iLQTS mothers seems to be lower if adjusted for gestational age compared to those of iLQTS fathers [6]. It is important to highlight that pregnant iLQTS women themselves are at an increased risk for cardiac events (CE) postpartum, particularly in case of a LQTS type 2 (LQTS2) [8-11]. The mothers have an alternated sleep pattern, lack of sleep, and an increased physical/emotional stress, which might lead to an increased sympathetic activity, with an increased gene-specific CE risk postpartum [9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The adrenergic nature of labor and delivery may lead to catecholaminergic polymorphic ventricular tachycardia in these patients. Furthermore, patients with congenital long QT syndrome are also at risk during a nine-month post-partum period 19 . Treatment with beta-blockers are the mainstay of therapy during pregnancy and in the post-partum period 19 .…”
mentioning
confidence: 99%
“…Furthermore, patients with congenital long QT syndrome are also at risk during a nine-month post-partum period 19 . Treatment with beta-blockers are the mainstay of therapy during pregnancy and in the post-partum period 19 . There is a lack of data for therapeutics that may be urgently needed intrapartum that may prolong the QT interval in susceptible patients.…”
mentioning
confidence: 99%